Pope Francis’ model - Osorio Torres, Juan Alberto (2017)
From the theology and anthropology of the diocese, a few months before the visit of the Supreme Pontiff to Peru (18-01-2018), the author warns, locates and explains the growing position of Pope Francis’ model in the recent developments of the Catholic Church. It examines the historical background and rootedness of this model among the dioceses of Latin America and the Caribbean, and reveals its theological and pastoral implications in the process of reform of the structures of the Church that the first Latin American pope convened in his Evangelii Gaudium (EG 2013). Meanwhile, and decisively, the Pope Francis’ model has succeeded at mending and exposing the oppositions, inertias and contradictions of the dominant pastoral theological model.